2001
DOI: 10.1016/s0736-5748(00)00067-8
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of cortical target induced by prenatal ionizing irradiation: effects on the lateral geniculate nucleus and on the retinofugal pathways

Abstract: Studies using neonatal surgical lesions to reduce the target area of the retina have supported the idea that developing axons show only a limited specificity in their targeting. This investigation tested whether retinogeniculate axons adjust for partial target depletion by repositioning of axons. We used adult Swiss mice exposed to gamma rays at the time when layer IV cells are generated in the ventricular zone (16 days of gestation). Nissl-stained brain sections were used for histological analyses in thalamus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…An expansion of the retinal projection to the pregeniculate nucleus was reported after lesion of the striate cortex (Weller & Kaas, 1989), but not after hemispherectomy (Théoret et al ., 2000). In mice prenatally irradiated at E16 (Schmidt et al ., 2001), the shrinkage of the posterior cortical territory is also accompanied by significant reduction of the dorsal LGN. Retinofugal axons reach the same territories as in normal mice and aberrant projections to the surrounding nuclei, in particular to LP, were not observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An expansion of the retinal projection to the pregeniculate nucleus was reported after lesion of the striate cortex (Weller & Kaas, 1989), but not after hemispherectomy (Théoret et al ., 2000). In mice prenatally irradiated at E16 (Schmidt et al ., 2001), the shrinkage of the posterior cortical territory is also accompanied by significant reduction of the dorsal LGN. Retinofugal axons reach the same territories as in normal mice and aberrant projections to the surrounding nuclei, in particular to LP, were not observed.…”
Section: Discussionmentioning
confidence: 99%
“…The second goal is to compare the state of the LGN and retinofugal projections in ferrets with early cortical lesions with the results of similar experiments in monkey (Boire et al ., 2000), mouse (Schmidt et al ., 2001) and rabbit (Murphy et al ., 1988). This is required in order to understand whether common principles of neural development and plasticity apply across species, and therefore whether the consequences of early lesions of the visual areas in animals can be extrapolated to humans.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that prenatal irradiation is a useful paradigm to selectively eliminate certain neuronal populations during development because young undifferen-tiated neurons are extremely radiosensitive (Hicks, 1953(Hicks, , 1958D'Amato and Hicks, 1965;D'Amato, 1982;Schmidt and Lent, 1987;Ferrer et al, 1993;Abreu-Villaça and Schmidt, 1999;Caparelli-Dáquer and Schmidt, 1999). In this sense, Schmidt et al (2001) showed that adult mice exposed to gamma radiation on E16 present severe shrinkage of the occipital cortex and a 75% reduction in the number of neurons of the DLGN. The occipital cortex, especially layers IV and III, are directly affected by irradiation (Schmidt and Lent, 1987;Abreu-Villaça and Schmidt, 1999), since their neurons are being generated on E16 (Caviness and Sidman, 1973;Caviness, 1982;Caviness et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, considering that DLGN neurons are generated earlier than E16, from E12 to E14 (Angevine, 1970), it is reasonable to suppose that this nucleus is not directly affected by radiation. Schmidt et al (2001) allowed irradiated mice to survive to adulthood and, as a consequence, they did not accompany the sequence of events induced by irradiation. In our study we investigated the DLGN of mice ranging from E17 to P15 after exposure to gamma radiation (3 Gy) on E16.…”
Section: Introductionmentioning
confidence: 99%